Analisis Strategi Pemasaran Usaha Rumahan (Studi Kasus Penggilingan Mie Pak Paidi Manna Kabupaten Bengkulu Selatan) - Ari yanto; Ida Anggriani; Zoniarti Zoniarti (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
Marketing strategy, a business will seek to improve marketing in the hope that sales will be better and increase than before. Marketing strategy or what is usually called SWOT (Strengths, Weaknesses, Opportunities, and Threats) is the systematic identification of various factors to determine the company's strategy. The purpose of this research was to find out the marketing strategy for a home-based business (a case study of Pak Paidi's noodle mill, South Bengkulu district). The type of research used in this research thesis is a qualitative method. The analytical method used in this study is the SWOT analysis method (strengths, weaknesses, opportunities, threats). The data obtained from the results of the research will be analyzed for strengths, weaknesses, opportunities, and threats to the implementation of Pak Paidi's noodle milling business strategy in order to increase buyer interest. the company uses a Growth Oriented Strategy. From the research results, the internal value is 5.26 and the external value is 5.25. This is because, in the SWOT analysis Cartesius diagram it is shown that the highest total score is in the first quadrant where the quadrant is a very profitable situation. After conducting research, Mr. Paidi's noodle milling business has many opportunities and strengths so that he can seize and take advantage of existing opportunities while minimizing weaknesses and overcoming various threats that exist in Mr. Paidi's business environment.